Notes on two Draconarius species (Araneae, Agelenidae) from Guizhou, China - Wang, Xiaoxiao; Wu, San’an; Li, Shuqiang (Zootaxa, 2012)
This research provides the first description of male Draconarius guizhouensis (Peng, Li & Huang, 2002) comb. n., whichis transferred from Coelotes. Our study also supported the following Draconarius synonyms: D. semilunatus Zhu & Chen,2009 syn. n. is a junior synonym of D. guizhouensis (Peng, Li & Huang, 2002) and D. grossus Zhu & Chen, 2009 syn. n. is a junior synonym of D. spirallus Xu & Li, 2007.